Comparative evaluation of 3D building model using UAV photogrammetry and terrestrial laser scanner (TLS) / Golwes Edson Gaong ... [et al.] - Gaong, Golwes Edson; Idris, Ahmad Norhisyam; Lau, Chong Luh; Ab Rahman, Abdul Aziz; Wan Mohamed Sabri, Wan Mohamed Syafuan; Abdul Jalil, Abdul Hadi (UiTM Press, 2025)
With the growing emphasis on sustainability and resource efficiency within the architectural, engineering, and construction (AEC) sectors, Unmanned Aerial Vehicles (UAVs) and Terrestrial Laser Scanner (TLS) have emerged as indispensable tools for the monitoring and inspection of building structures by using 3D modelling. This research is dedicated to assessing the quality and accuracy obtained from 3D modelling for a building and its structural components between UAV photogrammetry and TLS techniques. The investigation involved nadir and oblique flight missions for UAV data acquisition around the target structure, utilising six (6) Ground Control Points (GCPs), while TLS data collection employed direct georeferencing via the traversing method. The results revealed that TLS yielded superior surface reconstruction quality owing to its denser point cloud density, whereas UAV data met the requirements of numerous applications, offering a convenient and economically viable data acquisition solution. Regarding accuracy, a minimal disparity was observed for building objects discernible from both instruments, achieving centimetre-level accuracy. These findings not only highlighted the potential of UAVs and TLS in optimising 3D modelling processes but also offered practical insights for professionals engaged in urban planning, architectural design, and structural analysis endeavours.